SAPROLEGNIASIS OF BARBUS SHARPEYI , GUNTHER (BUNNEI FISH) IN BASRAH / IRAQ - AL-DUBOON, ABDUL-HAFIZ; AL –MUKHTAR, MUSTAFA A.; JASSIM, ABDUL AMER R.; BADGER, SANAA QASSEM; AL-ZWAR, JIHAD M. (Iraqi Journal of Aquaculture, 2022)
Among 600 bunnei fishes transferred from Qurna marshes to fish ponds at Basrah University/Marine Science Center, 211 fishes were infected with saprolegniasis during the period from January to March,2005 constituting a percentage of infection of 35.1% which was diagnosed by its clinical features and by direct examination with 10% KOH solution and by culture. The cultutred fungus was Saprolegnia parasitica.